A "Dual Career": Combining sport and studies - Stambulova, N. Harwood, C. (Frontiers for Young Minds, 2022)
School-aged athletes face the need to balance competitive sports and their studies. In doing so they follow what is called a dual-career pathway. Both pursuits take time and effort, both are expected to lead to success, and either could lead to a life-long career. A dual-career pathway begins when children start to play sports and might continue throughout the school years and beyond. Research shows that it is beneficial to combine sport and studies, but it is also challenging. How can kids optimally juggle their sport, studies, social, and private lives? How do they gain the benefits of a dual career and avoid harming their prospects in sport or school? This article explains what a dual career is, why it is important, and why it is difficult. It also describes the skills and strategies for coping with dual-career challenges and presents tips from researchers to achieve success in dual-career pursuits.